On project pedagogy: experience leading the individual to theory (International Seven Journal of Multidisciplinary, 2023)
This article-essay is about the pedagogy of projects: the experience leading the individual to theory. The proposal is to clarify that learning happens through empirical contact with reality and with the phenomena that happen in nature. Its scientific relevance lies in the fact that it presents a technical discussion about a study methodology that allows a direct, reciprocal, and simultaneous relationship between practice and theory. Its social relevance lies in making available to society a mechanism that exponentially increases students' learning gains, allowing them a pragmatic view of the syllabus with which they have academic contact. The methodology used for this research was the bibliographic one, added to the pedagogical and didactic practice of the authors in teaching. We tried to present a deep and wide discussion, in which the supremacy of experience over theory is advocated, in which the former leads the latter, expressing and communicating the acquired knowledge. Project Pedagogy arose from the need to develop a pedagogical work methodology that aimed at valuing the participation of the student and the educator in the learning- teaching process, considering that learning takes precedence over teaching. By proposing Project Pedagogy as a teaching methodology, this means ending the monopoly of the traditional teacher who decides and defines himself the content and the tasks to be developed and which truths should be considered and/or denied, valuing, within strict academic-scientific principles, what the students already know and respecting what they want to learn at that moment, aware that theproblem-situation raised is the leitmotiv of the experience to be put in evidence, culminating in learning. When we talk about project-based learning we are necessarily referring to the formulation of questions by the author of the project, by the individual who will build knowledge from a problem situation.